American environmentalism, sovereignty and the "immigration problem" - Hultgren, John, author; Stevis, Dimitris, advisor; MacDonald, Bradley, committee member; Chaloupka, William, committee member; Ishiwata, Eric, committee member; Browne, Kate, committee member (Colorado State University. Libraries, 2012)
Theorizing the relationship between sovereignty and nature has posed challenges to both scholars and activists. Some believe that sovereignty is a problematic institutional constraint that hampers the formulation of holistic solutions to ecological problems, while others contend that the norms, practices and institutions of sovereignty can be stretched in pursuit of ecological and social sustainability. Complicating this picture is the fact that the empirical contours of sovereignty have shifted of late, as the authority and control of the nation-state has been challenged by neoliberal globalization and the transboundary realities of many environmental challenges, creating a crisis of legitimacy that societal actors attempt to ameliorate in various ways. This dissertation begins from the observation that "nature" - the socially constructed ideal employed to capture the vast multiplicity of the non-human realm - is increasingly central to the process through which individuals, interest groups and social movements attempt to create more democratic, sustainable or ethical political communities and forms of governance. As environmental politics continue to gain traction within mainstream political discourses, environmentalists and non-environmentalists alike are inserting nature into struggles to reconfigure sovereignty toward a particular ecological and/or social ethos. In exploring this interaction, I ask: how do societal groups conceptualize and work to reconfigure the relationship between nature and sovereignty? And what are the social and ecological implications of the normative ideals that they attempt to institutionalize? In order to gain insight into these questions, I examine contemporary American debates over the environmental impacts of immigration. Discussions of the so-called "immigration problem" have been contentious for American greens, leading to significant division within environmentalist organizations, and surprising alliances with a variety of other societal interests. The individuals and organizations involved all attempt to challenge the status quo, but deploy vastly different conceptions of nature, political community and governance to do so. Turning to individuals and organizations who have taken public stances within this debate, I employ (1) textual analysis of websites and publications; (2) semi-structured interviews; and (3) content analysis, in considering the various discursive pathways through which environmental restrictionists and their opponents attempt to reconfigure sovereignty. Through this empirical analysis, I make the case that the discursive terrain on which the relationship between nature and sovereignty resides remains poorly understood - to the detriment of efforts to promote socially and ecologically inclusive polities.
Keywords: sovereignty; nation; nature; environmentalism; immigration